La medicina molecular. ¿es una utopía pensar en su aplicación clínica? - Aldunate O., Jorge; Nieto S., Elena (Revista Hospital Clínico Universidad de Chile, 1997)
In order to know better the diagnostics and the physiopathology of molecular, it's necessary to incorporate Molecular Biology techniques to an important group of illnesses, sorne of them are infectious pathologies and genetic illnesses.The knowledge of human metabolic ways or the specific enzymes that can be of molecular basis of the several man pathologies, is the MOLECULAR MEDICINE.Actually, at least exist three lines that use the Molecular Biology in order to understand medica[ problems.These main lines are: 1. Hereditary Illnesses, II. Viral and Bacteriology Diagnoses, and III. ldentification and the studies of Paternity.